2006
DOI: 10.1111/j.1538-7836.2005.01751.x
|View full text |Cite
|
Sign up to set email alerts
|

High post‐treatment platelet reactivity identified low‐responders to dual antiplatelet therapy at increased risk of recurrent cardiovascular events after stenting for acute coronary syndrome

Abstract: Summary. Background and objectives: Low response to antiplatelet therapy may be a risk factor for the development of ischemic complications in patients with non-ST segment elevation acute coronary syndrome (NSTE ACS) undergoing coronary stenting. Methods: We prospectively studied the platelet response to both clopidogrel and aspirin in 106 NSTE ACS consecutive patients undergoing percutaneous coronary intervention (PCI) with stenting. A single post-treatment blood sample was obtained just before PCI and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
250
3
8

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(271 citation statements)
references
References 32 publications
10
250
3
8
Order By: Relevance
“…Unfortunately, there was a trend towards increased 90 day rehospitalization rates due to recurrent thrombosis or bleeding in both the patients where no changes to therapy were made and patients where clopidogrel was discontinued without any thing to take its place. These results are similar to prior studies demonstrating that patients with low platelet inhibition are more likely to experience rethrombosis and ischemia than patients with higher levels of platelet inhibition [2][3][4][6][7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Unfortunately, there was a trend towards increased 90 day rehospitalization rates due to recurrent thrombosis or bleeding in both the patients where no changes to therapy were made and patients where clopidogrel was discontinued without any thing to take its place. These results are similar to prior studies demonstrating that patients with low platelet inhibition are more likely to experience rethrombosis and ischemia than patients with higher levels of platelet inhibition [2][3][4][6][7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 81%
“…Overall stent thrombosis was 3.1%; however this rate was 8.6% in nonresponders to clopidogrel compared to 2.3% in patients responding to clopidogrel (p<0.001) [7]. Similar results have been published in several other trials demonstrating the correlation between higher atherothrombotic events and lower platelet inhibition [8][9][10][11]. There are also studies using the VerifyNow P2Y 12 Test which demonstrate the correlation between higher atherothrombotic events and lower platelet inhibition [12][13][14][15][16].…”
Section: Introductionsupporting
confidence: 67%
“…Thus, some [5,8,9], but not other [25], very small studies suggest that patients with higher residual platelet reactivity after the initiation of clopidogrel therapy have more subsequent major adverse clinical outcomes. Higher doses of clopidogrel [26][27][28][29], or other antiplatelet therapy, may therefore be beneficial, especially in those patients with greater platelet reactivity to ADP, measured either before or after clopidogrel therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Response variability and resistance to clopidogrel therapy was first reported in 2003 [17]. Since then, many studies and registries suggested a relationship between high post-treatment platelet reactivity and clopidogrel nonresponsiveness in patients undergoing PCI, especially increased ischemic events including stent thrombosis [7,8,18,19]. All these data are from retrospective and prospective studies.…”
Section: Discussionmentioning
confidence: 99%